Advanced Materials and Sensors for Microphysiological Systems: Focus on Electronic and Electrooptical Interfaces. Issue 17 (14th March 2022) - Kavand, Hanie; Nasiri, Rohollah; Herland, Anna
Abstract: Advanced in vitro cell culture systems or microphysiological systems (MPSs), including microfluidic organ‐on‐a‐chip (OoC), are breakthrough technologies in biomedicine. These systems recapitulate features of human tissues outside of the body. They are increasingly being used to study the functionality of different organs for applications such as drug evolutions, disease modeling, and precision medicine. Currently, developers and endpoint users of these in vitro models promote how they can replace animal models or even be a better ethically neutral and humanized alternative to study pathology, physiology, and pharmacology. Although reported models show a remarkable physiological structure and function compared to the conventional 2D cell culture, they are almost exclusively based on standard passive polymers or glass with none or minimal real‐time stimuli and readout capacity. The next technology leap in reproducing in vivo‐like functionality and real‐time monitoring of tissue function could be realized with advanced functional materials and devices. This review describes the currently reported electronic and optical advanced materials for sensing and stimulation of MPS models. In addition, an overview of multi‐sensing for Body‐on‐Chip platforms is given. Finally, one gives the perspective on how advanced functional materials could be integrated into in vitro systems to precisely mimic human physiology. Abstract : Advanced in vitro cell culture or microphysiological systems (MPSs) recapitulate features of human tissues and are increasingly being used for drug development and disease modeling. Still, they are commonly based on standard polymers with minimal real‐time stimuli and read‐out capacity. This review describes how advanced materials and devices could enable a technology leap in reproducing in vivo‐like functionality and real‐time tissue monitoring.